How to implement backward Euler's method?

123 views (last 30 days)
I am trying to implement these formulas:
Forward Euler's method:
this is what I have tried:
x_new = (speye(nv)+ dt * lambda * L) * x_old;
Is there anything wrong with this? How can I calculate this using sparse operation?
Backward Euler's method:
I have tried this:
x_new = (speye(nv)- dt * lambda * L) \ x_old;
How to implement the backward part where the existing x is calculated based on the new x? Is it OK to use division?
=============================================================================
L is a sparse matrix like this:
full(L) =
-1.0000 0.2500 0.2500 0.2500 0.2500
0.3333 -1.0000 0.3333 0 0.3333
0.3333 0.3333 -1.0000 0.3333 0
0.3333 0 0.3333 -1.0000 0.3333
0.3333 0.3333 0 0.3333 -1.0000
also for other variable we have something like this:
nv = 5;
dt = 0.01;
lambda = 0.5;
x_old = [-4 0 5;
1 -5 5;
1 0 1;
1 5 5;
1 0 0]

Answers (1)

Dinesh Yadav
Dinesh Yadav on 27 Nov 2019

Categories

Find more on Mathematics in Help Center and File Exchange

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!